Experimental exposure to wood smoke: effects on airway inflammation and oxidative stress. Issue 5 (17th August 2007) - Barregard, L; Sällsten, G; Andersson, L; Almstrand, A-C; Gustafson, P; Andersson, M; Olin, A-C
Abstract : Background: Particulate air pollution affects cardiovascular and pulmonary disease and mortality. A main hypothesis about the mechanisms involved is that particles induce inflammation in lower airways, systemic inflammation and oxidative stress. Objectives: To examine whether short-term exposure to wood smoke in healthy subjects affects markers of pulmonary inflammation and oxidative stress. Methods: 13 subjects were exposed first to clean air and then to wood smoke in a chamber during 4-hour sessions, 1 week apart. The mass concentrations of fine particles at wood smoke exposure were 240–280 μg/m 3, and number concentrations were 95 000–180 000/cm 3, about half of the particles being ultrafine (<100 nm). Blood and breath samples were taken before and at various intervals after exposure to wood smoke and clean air and examined for exhaled nitric oxide and Clara cell protein in serum and urine, and malondialdehyde in exhaled breath condensate. Results: Exposure to wood smoke increased alveolar nitric oxide 3 hours post-exposure while malondialdehyde levels in breath condensate were higher both immediately after and 20 hours after exposure. Serum Clara cell protein was increased 20 hours after exposure. Conclusions: Wood smoke at levels that can be found in smoky indoor environments caused an inflammatory response and signs of increased oxidative stress in the respiratory tract, especially in the lower airways.